THE INFLUENCE OF GREEN ADVERTISING ON CUSTOMER LOYALTY SENSATIA BOTANICALS IN SURABAYA - Siahaya, Janice Carysa; Dananjaya, Yanuar (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
Green advertising has emerged as a strategic approach for businesses to promote their environmentally friendly products and practices while appealing to environmentally conscious consumers. This study aims to investigate the impact of green advertising on customer loyalty, focusing on Sensatia Botanicals in Surabaya, Indonesia. Through a combination of quantitative methods, data will be collected from customers to explore their perceptions of Sensatia Botanicals' green advertising initiatives and their effects on loyalty towards the brand. The findings of this research will contribute to the understanding of how green advertising influences customer loyalty in the context of a specific company operating in Surabaya. This study also provides insights for businesses seeking to develop effective green advertising strategies to enhance customer loyalty and contribute to sustainable business practices.